Death and Taxes : Does Taxation Matter for Firm Survival? - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2019)
This paper investigates the impact of taxation on firm survival, using hazard models and a large-scale panel dataset on over 4 million nonfinancial firms from 21 countries over the period 1995-2015. We find ample evidence that a lower level of effective marginal tax rate improves firms' survival chances. This result is not only statistically but also economically important and remains robust when we partition the sample into country subgroups. The effect of taxation on firms' survival probability is found to exhibit a non-linear pattern and be stronger in developing countries than advanced economies. These findings have important policy implications for the design of corporate tax systems. The challenge is not simply reducing the statutory tax rate, but to level the playing field for all firms by rationalizing differentiated tax treatments across sectors, asset types and sources of financing.